Probing the role of an invariant active site His in family GH1 β-glycosidases. (1st January 2019) - Strazzulli, Andrea; Perugino, Giuseppe; Mazzone, Marialuisa; Rossi, Mosè; Withers, Stephen G.; Moracci, Marco
Abstract: The reaction mechanism of glycoside hydrolases belonging to family 1 (GH1) of carbohydrate-active enzymes classification, hydrolysing β-O-glycosidic bonds, is well characterised. This family includes several thousands of enzymes with more than 20 different EC numbers depending on the sugar glycone recognised as substrate. Most GH1 β-glycosidases bind their substrates with similar specificity through invariant amino acid residues. Despite extensive studies, the clear identification of the roles played by each of these residues in the recognition of different glycones is not always possible. We demonstrated here that a histidine residue, completely conserved in the active site of the enzymes of this family, interacts with the C2-OH of the substrate in addition to the C3-OH as previously shown by 3 D-structure determination.